The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1164/rccm.201804-0678oc
|View full text |Cite
|
Sign up to set email alerts
|

Early Plasma Matrix Metalloproteinase Profiles. A Novel Pathway in Pediatric Acute Respiratory Distress Syndrome

Abstract: Pediatric ARDS patients have specific plasma MMP profiles associated with inflammation, endothelial injury, morbidity, and mortality. MMPs may play a role in the pathobiology of children with ARDS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
42
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 67 publications
3
42
0
Order By: Relevance
“…Previous research showed that the expression of MMPs was correlated with the progression of ARDS. The enhanced expression of MMPs was related to inflammation-induced endothelial injury and impaired oxygenation in ARDS [ 81 , 82 ]. Another study revealed that MMP inhibitors suppressed MMP expression in plasma and lung tissue, decreased inflammatory mediator release, and attenuated lung inflammatory injury [ 83 , 84 ].…”
Section: Role Of Neutrophils In Ardsmentioning
confidence: 99%
“…Previous research showed that the expression of MMPs was correlated with the progression of ARDS. The enhanced expression of MMPs was related to inflammation-induced endothelial injury and impaired oxygenation in ARDS [ 81 , 82 ]. Another study revealed that MMP inhibitors suppressed MMP expression in plasma and lung tissue, decreased inflammatory mediator release, and attenuated lung inflammatory injury [ 83 , 84 ].…”
Section: Role Of Neutrophils In Ardsmentioning
confidence: 99%
“…Pulmonary fibrosis is a well-recognized feature of acute respiratory distress syndrome (ARDS) [1][2][3], and lipopolysaccharide (LPS) is a considerable factor causing sepsisassociated ARDS and pulmonary fibrosis [4][5][6]. However, the related mechanisms are not fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…In this study we propose activation of TREK-1 K + channels as a potentially new therapeutic approach against HALI, since currently no targeted interventions exist that translate into improved patient outcomes. Recent in vitro studies suggest that overexpression of certain microRNAs (miR16, miR21-5) may protect cultured AT2 cells against HO-induced apoptosis [53][54][55] , and multiple biomarker studies have aimed at predicting the risk of HALI in patients 56,57 . In addition, neutralizing therapies against individual cytokines, including IL-6, TNF-α and CCL-2, have yielded variable results at best in improving inflammatory responses [58][59][60][61] .…”
Section: Discussionmentioning
confidence: 99%